Social capital as good culture - Guiso, Luigi 1955-; Sapienza, Paola; Zingales, Luigi 1963- (National Bureau of Economic Research, 2007)
To explain the extremely long-term persistence (more than 500 years) of positive historical experiences of cooperation (Putnam 1993), we model the intergenerational transmission of priors about the trustworthiness of others. We show that this transmission tends to be biased toward excessively conservative priors. As a result, societies can be trapped in a low-trust equilibrium. In this context, a temporary shock to the return to trusting can have a permanent effect on the level of trust. We validate the model by testing its predictions on the World Values Survey data and the German Socio Economic Panel. We also present some anecdotal evidence that differences in priors across regions are reflected in the spirit of the novels that originate from those regions.